SHARING ECONOMY AND ECONOMIC LIBERALISM: NEW CONTEXT FOR PLATFORM COOPERATIVISM - Menezes, Nagao; Francisco, Daniel; Rivera, González; Vanessa, Tatiana (International Journal of Cooperative Law, 2023)
The current technological advance, driven by the generalization in the use of information and communication technologies and social networks, together with the dynamism of economic markets, has favored the emergence of the collaborative economy phenomenon.Its evolution has led us to the implementation of large digital mediation platforms that have created new business models that capitalize on the collaboration of users and appropriate the capital gains generated by their interaction. In addition, they have become promoters of a supposed new way of working that, in reality, is one more level of the flexibilization trend of the labor market and its consequent precariousness of labor relations. In fact, the existence of an employment relationship within these platforms is denied under a friendly discourse focused on freedom, proactivity, and cooperation. In this work, we intend to reflect on the concept of the collaborative economy and its raison d'être, the context in which this phenomenon occurs, and the consequences that begin to manifest themselves in the economy in general and in the labor market in particular.